Full conversion from ohmic to runaway electron driven current via massive gas injection in the TCV tokamak. (1st July 2022) - Decker, J.; Papp, G.; Coda, S.; Duval, B.P.; Sheikh, U.; Blanchard, P.; Choi, D.; Galperti, C.; Calacci, L.; Carnevale, D.; Ficker, O.; Gobbin, M.; et al.
Abstract: Full conversion from ohmic to runaway electron (RE) driven current was observed in the tokamak à configuration variable (TCV) following massive injection of neon through a disruption mitigation valve into a low-density limited circular plasma. Following a partial disruption, a stable 200 kA RE beam is maintained for more than 1 s. Controlled ramp-down of the RE beam with adjustable decay rate was demonstrated. Control of the beam vertical position was achieved down to a RE current of 20 kA. RE beam formation is observed in elongated plasma configurations up to κ = 1.5. A reproducible scenario for RE beam generation without loss of circulating current is of particular interest for disruption modelling applications.